2022
DOI: 10.1371/journal.pntd.0010365
|View full text |Cite
|
Sign up to set email alerts
|

Combining rapid diagnostic tests to estimate primary and post-primary dengue immune status at the point of care

Abstract: Background Characterising dengue virus (DENV) infection history at the point of care is challenging as it relies on intensive laboratory techniques. We investigated how combining different rapid diagnostic tests (RDTs) can be used to accurately determine the primary and post-primary DENV immune status of reporting patients during diagnosis. Methods and findings Serum from cross-sectional surveys of acute suspected dengue patients in Indonesia (N:200) and Vietnam (N: 1,217) were assayed using dengue laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This is consistent with assays having been developed for the diagnosis of dengue in patients with acute febrile illness and differentiation of primary vs. post-primary dengue (where concentrations of IgG are usually higher compared to those seen long after convalescence). Previous studies have found that some ELISAs which detect dengue IgG can also be insensitive, particularly in individuals who have lower titres of neutralising antibodies and/or where there is a monotypic antibody profile [ 22 , 23 ]. Importantly, the latter group of individuals are most likely to benefit most from vaccination but would be denied this if pre-vaccination screening was falsely negative.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with assays having been developed for the diagnosis of dengue in patients with acute febrile illness and differentiation of primary vs. post-primary dengue (where concentrations of IgG are usually higher compared to those seen long after convalescence). Previous studies have found that some ELISAs which detect dengue IgG can also be insensitive, particularly in individuals who have lower titres of neutralising antibodies and/or where there is a monotypic antibody profile [ 22 , 23 ]. Importantly, the latter group of individuals are most likely to benefit most from vaccination but would be denied this if pre-vaccination screening was falsely negative.…”
Section: Discussionmentioning
confidence: 99%
“…After Dengvaxia recipients presented with symptoms compatible with dengue at any health facility in the Philippines ( 3 ), blood samples were collected and sent to RITM, the national reference laboratory, for diagnostic testing. Participants testing positive, using either DENV RT-PCR or Panbio dengue IgM-capture ELISA (Abbott, South Korea), were defined as laboratory-confirmed acute dengue cases, and participants testing negative using both tests were classified as non-acute dengue or other febrile illnesses ( 38 , 39 ). The day of symptom (fever) onset was designated as day 1.…”
Section: Methodsmentioning
confidence: 99%
“…Various RDTs have been tested and some have shown reasonable sensitivity and specificity [57]. Primary and postprimary DENV immune status of reporting patients can be estimated at the point of care by combining NS1, IgM, and IgG RDTs and considering the days since symptoms onset [58]. Dengue IgG RDTs and the Panbio ELISA exhibited favourable specificities (99-100%).…”
Section: Tetravalent Live-attenuated Recombinant Dengue Vaccine (Cyd-...mentioning
confidence: 99%